Geometry of the Intervertebral Volume and Vertebral Endplates of the Human Spine - van der Houwen, E. B. (Springer US, 2009)
Replacement of a degenerated vertebral disc with an artificial intervertebral disc (AID) is currently possible, but poses problems, mainly in the force distribution through the vertebral column. Data on the intervertebral disc space geometry will provide a better fit of the prosthesis to the vertebrae, but current literature on vertebral disc geometry is very scarce or not suitable. In this study, existing CT-scans of 77 patients were analyzed to measure the intervertebral disc and vertebral endplate geometry of the lumbar spine. Ten adjacent points on both sides of the vertebrae (S1-superior to T12-inferior) and sagittal and transverse diameters were measured to describe the shape of the caudal and cranial vertebral planes of the vertebrae. It was found that the largest endplate depth is located in the middle or posterior regions of the vertebra, that there is a linear relationship between all inferior endplate depths and the endplate location (p < 0.0001) within the spinal column, and that the superior endplate depth increases with age by about 0.01 mm per year (p < 0.02). The wedge angle increases from T12-L1 to L5-S1. The results allow for improvement of the fit of intervertebral disc-prostheses to the vertebrae and optimized force transmission through the vertebral column.